A Night at the Pictures : A Christmas Carol et la séduction du simulacra - Florent Christol (Cahiers Victoriens et Edouardiens)
A Christmas Carol, which stands as one of the most popular works of Dickens, is not highly ranked by literary critics and scholars. The main reason for this somewhat paradoxical fate is that Dickens is known for his contribution to the novel, a genre preoccupied with issues of realism and the denunciation of social ills. But A Christmas Carol, as a ghost story, unashamedly belongs to the popular tradition of romance, a genre known to foster pathos and lull the reader into an intellectual slumber through exotic images of far-away lands and heroic adventures. In this paper, we would like to show how Dickens attempts in his text to reconcile these two conflicting views. Indeed, A Christmas Carol can be read as an essay on the potential intermingling of novel and romance. In this « ghost story of Christmas, » romance assumes the familiar shape of the Spirits of Christmas, who show Scrooge images of the poor and the destitute and make him aware of a reality to which he was completely blind, maybe because reality can only be apprehended through a representation, its projection on a screen through which it becomes visible.